2020
DOI: 10.7455/ijfs/9.2.2020.a8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable film development by nisin Z addition into hydroxypropylmethylcellulose matrix for mozzarella cheese preservation

Abstract: Currently, improvement of food preservation has been a substantial challenge for industries to increase shelf-life of products and to maintain food quality during storage. These goals are often tied to the sustainable tendency for use of eco-friendly packaging to store these products without loss of the packaging features. Therefore, the aim of this study was to produce biodegradable antimicrobial films by the incorporation of nisin Z peptide under different concentrations (0 %, 5 %, 10 %, 15 % and 20 % wt.) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Biodegradable antimicrobial films based on HPMC (hydroxypropylmethylcellulose) incorporated with nisin Z were developed by Freitas et al (2020) [ 135 ] and applied to sliced mozzarella cheese. It was observed that nisin presented antimicrobial activity against gram-positive bacteria, such as Staphylococcus aureus and Listeria innocua , but also inhibited gram-negative bacteria, such as Salmonella enterica .…”
Section: Application and Effects Of Nisin Incorporated Packaging Mate...mentioning
confidence: 99%
“…Biodegradable antimicrobial films based on HPMC (hydroxypropylmethylcellulose) incorporated with nisin Z were developed by Freitas et al (2020) [ 135 ] and applied to sliced mozzarella cheese. It was observed that nisin presented antimicrobial activity against gram-positive bacteria, such as Staphylococcus aureus and Listeria innocua , but also inhibited gram-negative bacteria, such as Salmonella enterica .…”
Section: Application and Effects Of Nisin Incorporated Packaging Mate...mentioning
confidence: 99%
“…Biodegradable food packaging is one of the best efforts to solve the problems of nonbiodegradable-based counterpart as the latter tend to remain in the environment for hundreds of years [81]. Most authors have reported that the modification of biodegradable polymers displayed improvement in the mechanical, thermal, barrier, and antimicrobial properties while maintaining the stability and extending the shelf life of packaged foods such as fish, cheese, and fruits [82][83][84][85]. e utilization of biodegradable polymer seems to be a promising material for food packaging.…”
Section: Introductionmentioning
confidence: 99%